2019
DOI: 10.1186/s12876-019-0975-3
|View full text |Cite
|
Sign up to set email alerts
|

Tumor location as an indicator of survival in T1 resectable pancreatic ductal adenocarcinoma: a propensity score-matched analysis

Abstract: Background The latest 8th edition of the AJCC staging system emphasizes the importance of tumor size however, the clinical significance of the combination of tumor location with tumor size remains unknown. Methods We conducted this study to investigate the prognostic role of tumor location in T1 resectable pancreatic ductal adenocarcinoma (PDAC). Resectable PDAC patients from Surveillance, Epidemiology, and End Results (SEER) database (2004–2014) were selected for the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 32 publications
1
21
0
Order By: Relevance
“…Thus, earlier T categories (T1 and T2) demonstrated significantly worse median survival and 5-year survival (24 months and 21.8%) in the PHU group than in the PBT group (34 months and 37.2%) (p = 0.003). Meng et al [12] also found that resected pancreatic head cancers had worse outcomes in the earlier T stages, but significant difference was observed only for the T1 stage.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Thus, earlier T categories (T1 and T2) demonstrated significantly worse median survival and 5-year survival (24 months and 21.8%) in the PHU group than in the PBT group (34 months and 37.2%) (p = 0.003). Meng et al [12] also found that resected pancreatic head cancers had worse outcomes in the earlier T stages, but significant difference was observed only for the T1 stage.…”
Section: Discussionmentioning
confidence: 95%
“…However, pancreatic cancer is usually treated according to the location. Many studies investigated pancreatic cancers separately according to the location [ 2 , 4 , 8 , 9 , 10 , 11 , 12 ]. Furthermore, many studies investigated whether the subjects underwent distal pancreatectomy or pancreatoduodenectomy, which is a reflection of the location of the tumor [ 13 , 14 , 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A large cohort analysis using the National Cancer Database of the United States from 1998 to 2011 demonstrated that among 40,980 cases of resected PDAC, pancreatic head cancers had advanced tumor stage, higher nodal positivity, worse tumor grade and poorer overall survival than pancreatic body/tail cancers [2]. A recent strictly propensity score-matched (e.g., race, gender, marital status, TMN stage and pathology grade) study including 4,571 resected T1 stage PDACs from Surveillance, Epidemiology, and End Results (SEER) database (2004-2014) provided the best evidence showing the prognostic value of tumor location in early-stage PDACs up to now [8]. They found that patients with pancreatic head cancer had a worse prognosis compared to those with pancreatic body/tail cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Pancreatic body and tail tumors present late as they do not have symptoms in the early stages [33]. Thus, the pancreatic body and tail tumors are likely to invade beyond the pancreas.…”
Section: Discussionmentioning
confidence: 99%